Plasma Heating of Tokamak by Microwaves at Electron Cyclotron Resonance Heating (ECRH) - Baghdad Science Journal (مجلة بغداد للعلوم, 2008)
The brief description to the theory of propagation of electromagnetic waves in plasma was done. The cutoff and resonance regions have been showed. The principles of plasma heating at electron cyclotron resonance (ECRH) method have been mentioned. The numerical simulation to three different station: Tosca station in United Kingdom, ISX-B station in USA and T-10 station in Russia had been done. The optical depth and the friction of energy absorbed A have been calculated. The simulation results indicate that both and A are increase with size of the tokamak and it is possible to obtain full absorption in large tokamak.